ANALISIS YURIDIS KEDUDUKAN NOTARIS DALAM MENGUNGKAPKAN PEMILIK MANFAAT (BENEFICIAL OWNERSHIP) DALAM PEMBUATAN AKTA NOTARIS - VELLICHIA LAWRENCE (Jurnal Perspektif Hukum, 2021)
A notary as a public official, in drawing up authentic deeds particularly related to corporation, is also obliged to implement Know Your Beneficial Owner Principle which is not stipulated in the Notarial Act. On one hand, a notary plays an importnant role to reveal the beneficial ownership of a corporation, on the other hand transparency in revealing beneficial ownership has to be based on honest and clear information from delegation of the corporation since the existence of beneficial ownership cannot be fully detected by the notary. The research problems are how the notary’s liability for the drawing up of notarial deeds, why it is necessary to reveal the beneficial ownership of a corporation, and how about the status of a notary in revealing the beneficial ownership in drawing up notarial deeds. This research employs normative juridical method. The data are collected through library research, which materials or data obtained are systematically organized and analyzed by scientific logical procedures that is qualitative. The results are expected to be able to answer the research problems and to solve them.